Penerapan Applikasi Edukasi Komputer Untuk Meningkatkan Hapalan Abjad Di Tk Yapita Surabaya - Lianatus Shofia; Valentine Aqwarinna Gempita; Nopitasari; muchamad arif (Universitas Narotama, 2019)
This study aims to determine the effectiveness of the educational application that is applied in Yapita Kindergarten Surabaya. The author uses descriptive qualitative methods. The author focuses on how to apply computer education applications to help students memorize the alphabet. The author made observations during the 3x meeting. Each meeting, they get a different computer education application game but the contents of the material are the same. The application has been installed on every school computer that has been adapted to the material being taught. The subject of the research was TK A, amounting to 30 students. Each student uses the computer provided at each meeting for 30 minutes. The results showed that learning media through varied computer programs in a game will make children more excited and enthusiastic to learn because it is not boring. However, for children who do not understand the alphabetical order, they will experience difficulties and confusion. Also, children who have poorly trained physics will experience difficulties when using the mouse. Keywords: : computer application, alphabetical, enthusiastic, soft motoric